2015
DOI: 10.1007/s11101-015-9424-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of fatty acid biosynthetic pathway in sesame (Sesamum indicum L.): assembling tools to develop nutritionally desirable sesame seed oil

Abstract: Vegetable oils are an essential component of human diet, in terms of their health beneficial roles. Despite their importance, the fatty acid profile of most commonly used edible oil seed crop plants are imbalanced; this skewed ratio of fatty acids in the diet has been shown to be a major reason for the occurrence of cardiovascular and autoimmune diseases. Until recently, it was not possible to exert significant control over the fatty acid composition of vegetable oils derived from different plants. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…The elevated production of PUFAs such as C20:4 and C20:5 in the study could be due to the elevated supply of fatty acid precursors by overexpressed PtAGPAT. Bhunia et al [ 38 ] reported that the content of fatty acids such as C20:4 and C20:5 were significantly influenced by the availability of precursor molecules. Fatty acids synthesized in the chloroplast were transported to cytosol where CoA was attached by long-chain fatty acyl-CoA synthetase and subsequent for esterification.…”
Section: Resultsmentioning
confidence: 99%
“…The elevated production of PUFAs such as C20:4 and C20:5 in the study could be due to the elevated supply of fatty acid precursors by overexpressed PtAGPAT. Bhunia et al [ 38 ] reported that the content of fatty acids such as C20:4 and C20:5 were significantly influenced by the availability of precursor molecules. Fatty acids synthesized in the chloroplast were transported to cytosol where CoA was attached by long-chain fatty acyl-CoA synthetase and subsequent for esterification.…”
Section: Resultsmentioning
confidence: 99%
“…The FAD3 is a microsomal enzyme located in the ER facing the cytosol, whereas FAD7 and FAD8 are plastidial enzymes located in the inner membrane of the chloroplast envelope. In addition, FAD7 can also be found in the thylakoid of the chloroplasts ( Andreu et al, 2007 ; Bhunia et al, 2016 ). In contrast to this, FAD4 and FAD5 produce C16:1 from C16:0 in particular for phosphatidyl glycerol and mono-galactosyldiacylglycerols (MGDG), respectively ( Murphy and Piffanelli, 1998 ).…”
Section: Fatty Acid Desaturase Genesmentioning
confidence: 99%
“… General biosynthetic pathway of fatty acids and lipids in plants [PC phosphocholine; FAD fatty acid desaturase: KAS ketoacyl-ACP synthase] ( Guan et al, 2012c : Suresha et al, 2012 ; Bhunia et al, 2016 ). …”
Section: Significance and Key Role Of Fad2mentioning
confidence: 99%
See 2 more Smart Citations